PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUASAN SERTA IMPLIKASI PADA LOYALITAS NASABAH PT. RABOBANK INTERNASIONAL INDONESIA (Studi Kasus Pada Produk CASA dan DEPOSITO di Cabang Tanah Abang Jakarta) - Rusmantowi, Ahmad (Operations Excellence: Journal of Applied Industrial Engineering, 2016)
Abstract. The aim of this research is to find out of the effect of quality products and promotion towards customer satisfication and implication to customer loyality. The respondents on this research are customers of CASA and time deposit on Rabobank Tanah Abang Branch, and they have become customer for at least 12 months. The number of respondents is set of 100 respondents by using sampling technique. This research used analysis of Structural Equation Modeling (SEM). The results showed that: There is a positive correlation towards quality products with customer‘s satisfaction, promotion to customer‘s satisfaction, quality product and promotion of customer‘s satisfaction, product with the customer‘s loyalty, promotion to customer‘s loyalty, and customer‘s satisfaction. Quality product, promotion towards the satisfication and loyality custumer, and there is no positive and significant correlation of quality product, promotion towards the loyality customer‘s through the customer‘s satisfaction as the intervening variable. Recommended for further researchers to expand the scope of the research is not just only one Rabobank Indonesia Branch but include of the others Rabobank Indonesia Branchs. Management of Rabobank Indonesia should to conduct evaluation and improved the service in case of responsiveness by giving special training for customer service to minimize complaintin order to increase satisfication and customer loyality. Keywords: Quality Product, Promotion, Satisfaction, and Customer Loyalty